Comparative and phylogenetic analyses of the chloroplast genome reveal the taxonomy of the Morus genus - Zeng, Qiwei; Chen, Miao; Wang, Shouchang; Xu, Xiaoxiang; Li, Tian; Xiang, Zhonghuai; He, Ningjia (Frontiers in Plant Science, 2022)
Mulberry (genus Morus) is an economically important woody plant with an altered ploidy level. The variable number of Morus species recognized by different studies indicates that the genus is in need of revision. In this study, the chloroplast (CP) genomes of 123 Morus varieties were de novo assembled and systematically analyzed. The 123 varieties represented six Morus species, namely, Morus alba, Morus nigra, Morus notabilis, Morus rubra, Morus celtidifolia, and Morus serrata. The Morus CP genome was found to be 158,969~159,548 bp in size with 125 genes, including 81 protein coding, 36 tRNA, and 8 rRNA genes. The 87 out of 123 mulberry accessions were assigned to 14 diverse groups with identical CP genome, which indicated that they are maternally inherited and share 14 common ancestors. Then 50 diverse CP genomes occurred in 123 mulberry accessions for further study. The CP genomes of the Morus genus with a quadripartite structure have two inverted repeat (IR) regions (25,654~25,702 bp) dividing the circular genome into a large single-copy (LSC) region (87,873~88,243 bp) and small single-copy (SSC) region (19,740~19,994 bp). Analysis of the phylogenetic tree constructed using the complete CP genome sequences of Morus revealed a monophyletic genus and that M. alba consisted of two clades, M. alba var. alba and M. alba var. multicaulis. The Japanese cultivated germplasms were derived from M. alba var. multicaulis. We propose that the Morus genus be classified into six species, M. nigra, M. notabilis, M. serrata, M. celtidifolia, M. rubra, and M. alba with two subspecies, M. alba var. alba and M. alba var. multicaulis. Our findings provide a valuable resource for the classification, domestication, and breeding improvement of mulberry.